Combined grazing with goats and sheep in lowered caatinga: pasture and animal performances - Leite, Eneas Reis; Araújo Filho, João Ambrósio de; Pinto, Fernando Cela (Pesquisa Agropecuaria Brasileira, 1995)
The effect of combined grazing with goats and sheep on diet and animal response in lowered caatinga was studied in Sobral, Ceará, Brazil. Sheep consumed more grass and less woody species leaves than goats. Weight gain (g/head/day) was not different (P>0.05) between animal species and was not affected by kind of combined grazing. Live weight production (kg/ha/year) was 19.8 for single goats, 18.8 for single sheep, and 15.7 for the combination of the two species. Carcass yield was similar in the two animal species, both in single and combined grazing. lt was concluded that the combined grazing with goats and sheep does not provide advantages at the animal performance standpoint, and is not recommended to the studied region.